State disparities in colorectal cancer mortality patterns in the United States - Naishadham, D.; Lansdorp_Vogelaar, Iris; Siegel, R.; Cokkinides, V.; Jemal, A. (American Association for Cancer Research Inc, 2011)
Background: Colorectal cancer (CRC) mortality rates have been decreasing for many decades in the United States, with the decrease accelerating in the most recent time period. The extent to which this decrease varies across states and its influence on the geographic patterns of rates is unknown. Methods: We analyzed the temporal trend in age-standardized CRC death rates for each state from 1990 to 2007 using joinpoint regression. We also examined the change in death rates between 1990-1994 and 2003-2007 using rate ratios with 95% confidence intervals and illustrated the change in pattern using maps. The relationship between the change in mortality rates and CRC screening rates for 2004 by state was examined using Pearson's correlation. Results: CRC mortality rates significantly decreased in all states except Mississippi between 1990 and 2007 based on the joinpoint model. The decrease in death rates between 1990-1994 and 2003-2007 ranged from 9% in Alabama to greater than 33% in Massachusetts, Rhode Island, New York, and Alaska; Mississippi and Wyoming showed no significant decrease. Generally, the northeastern states showed the largest decreases, whereas southern states showed the smallest decreases. The highest CRC mortality rates shifted from the northeastern states during 1990 to 1994 to the southern states along the Appalachian corridor during 2003 to 2007. The decrease in CRC mortality rates by state correlated strongly with uptake of screening (r = -0.65, P < 0.0001). Conclusions: Progress in reducing CRC mortality varies across states, with the Northeast showing the most progress and the South showing the least progress. Impact: These findings highlight the need for wider dissemination of CRC screening.